Certificación sostenible , como un aporte de calidad en la prestación de servicios turísticos caso: “la trenza del Valle de Tenza ” (2012)
In a global context, sustainable tourism, according to Londoño (2010), simultaneously satisfies the expectations of visitors and potentiates its opportunities in the future. This tourism is one of the activities that promote social, economic and environmental development that requires partnerships between the groups of involved agents, in order to give life to the principles of sustainability. This article presents the main features of certification stamps in sustainable processes and the guidelines of the Colombian regulations applicable to the tourist program “The braid of the Tenza Valley”.